Analisis Faktor-Faktor Yang Mempengaruhi Penyaluran Dana Bank Syariah: Studi kasus PT Bank Syariah Mandiri - Risma, Risma; Roestiono, Harry; Suharmiati, Suharmiati (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to determine the effect of NPF, ROA and BOPO on Fund Distribution. This research was conducted using the method of collecting and processing financial report data for the 2005-2020 period of Bank Syariah Mandiri based on a predetermined sample using a saturated sample. This study used a data test tool, namely the classical assumption test and the data were analyzed using multiple linear regression analysis. The results of this study are as follows: Partially the Non-Performing Financing Ratio has a significant effect on the distribution of funds, the significance value is -2.971 <0.012. Return on Assets has a significant effect on the distribution of funds with a significance value of -2.361 <0.036. Operational Expenses Operational income has no significant effect on the distribution of funds, the significance value is 1.050> 0.314. Simultaneously, the effect of NPF<ROA, and BOPO has a significant effect on Fund Distribution with a significance value of 0.012<0.05. The value of Adjusted R2 is 0.479, which means that the three independent variables affect the dependent variable by 0.479 (47.9%) and the rest is influenced by other variables.